2020
DOI: 10.1002/chem.202001815
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Chlorine from Chlorosulfonium Salts: A Highly Chemoselective Reduction of Sulfoxides

Abstract: Herein, we describe a selective late‐stage deoxygenation of sulfoxides based on a novel application of chlorosulfonium salts and demonstrate a new process using these species generated in situ from sulfoxides as the source of electrophilic chlorine. The use of highly nucleophilic 1,3,5‐trimethoxybenzene (TMB) as the reducing agent is described for the first time and applied in the deoxygenation of simple and functionalized sulfoxides. The method is easy to handle, economic, suitable for gram‐scale operations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…4-(Propylthio)phenol (5w, CAS: 18979-80-1). 24 The reaction was conducted with propane-1-thiol (27.2 μL, 0.3 mmol), cyclohexane-1,4-dione (56 mg, 0.5 mmol), I 2 (50.8 mg, 0.2 mmol), Na 3 PO 4 (32.8 mg, 0.2 mmol), and o-xylene (1.5 mL). The residue was purified by column chromatography on silica gel (PE/EtOAc = 3:1) to give 5w as yellow liquid; yield: 37.8 mg (75%).…”
Section: -((4-isopropylphenyl)thio)phenol (5b)mentioning
confidence: 99%
“…4-(Propylthio)phenol (5w, CAS: 18979-80-1). 24 The reaction was conducted with propane-1-thiol (27.2 μL, 0.3 mmol), cyclohexane-1,4-dione (56 mg, 0.5 mmol), I 2 (50.8 mg, 0.2 mmol), Na 3 PO 4 (32.8 mg, 0.2 mmol), and o-xylene (1.5 mL). The residue was purified by column chromatography on silica gel (PE/EtOAc = 3:1) to give 5w as yellow liquid; yield: 37.8 mg (75%).…”
Section: -((4-isopropylphenyl)thio)phenol (5b)mentioning
confidence: 99%
“… 37 For example, some sulfide-containing bioactive molecules, such as sulindac sulfide (anti-inflammatory drug) and ufiprazole (antiulcer drug), are synthesized by the deoxygenation of sulfoxide analogues. 38 , 39 Molecular hydrogen (H 2 ) is the most efficient reducing agent for deoxygenating sulfoxides to sulfides because water is formed as the sole byproduct. Although some precious metal NPs promote the deoxygenation of sulfoxides under mild conditions (e.g., atmospheric H 2 pressure), catalysis using precious metal phosphides has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…The deoxygenation of sulfoxides to sulfides is one of the important reactions in organic chemistry. , Recently, sulfoxides have served as effective directing groups in catalytic C–H functionalizations. Following functionalization, sulfoxide groups can be removed through deoxygenation, followed by desulfurization. , Deoxygenation of sulfoxides also plays a crucial role in the pharmaceutical chemistry . For example, some sulfide-containing bioactive molecules, such as sulindac sulfide (anti-inflammatory drug) and ufiprazole (antiulcer drug), are synthesized by the deoxygenation of sulfoxide analogues. , Molecular hydrogen (H 2 ) is the most efficient reducing agent for deoxygenating sulfoxides to sulfides because water is formed as the sole byproduct. Although some precious metal NPs promote the deoxygenation of sulfoxides under mild conditions (e.g., atmospheric H 2 pressure), catalysis using precious metal phosphides has not been reported to date. In this study, we investigated the effects of phosphorus (P)-alloying on NPs made of Pt, Pd, Rh, and Ru and found that the alloying significantly improved the catalytic activity of precious metal NPs for the deoxygenation of sulfoxides using H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…We have recently faced these problems. Our recent work on the deoxygenation of sulfoxides is one of the most general and straightforward methods reported [10]. Unfortunately, it needs dichloromethane or chloroform as solvents and always produces a stoichiometric amount of chorotrimethoxybenzene, which should be separated by chromatography.…”
Section: Introductionmentioning
confidence: 99%